Comparison of fish communities between natural and reforested mangrove habitats in Cogtong Bay, Bohol, Philippines - Polohan, Bernice Buot; Ikejima, Kou; Pedersen, Ole; Gallardo, Wenresti G.; Primavera, Jurgenne; Danish International Development Assistance (DANIDA) and Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2005)
The abundance, biomass, diversity and community structure of fish in natural and reforested natural mangrove habitats were studied in Cogtong Bay, Bohol, Philippines to determine whether a reforested mangrove habitat can function as well as the natural mangrove habitat. After a history of heavy exploitation of mangroves along the bay, mangroves have been rehabilitated through reforestation. Over the past years, several areas of mangroves destroyed or degraded by wood harvesting have been planted with mangrove seedling using common local species. A monospecific stand of Rhizophora mucronata was compared with a natural and multi-species mangrove habitat which is relatively undisturbed. A total of 734 individuals, comprising 21 species (11 families) were collected using set stake nets. Mean abundances of the fish found in the natural and reforested habitats, respectively, were 0.26 and 0.23 individuals m-2 . The mean biomass of the fish community was 2.11 and 1.13 g m-2 for the natural and reforested mangroves, respectively. In terms of abundance, Apogonidae, Atherinidae, Hemiramphidae and Mugilidae were the dominant families. Fish abundance and species richness (using data pooled for all sampling rounds) were not significantly different between the two habitats. Cluster and ordination analysis based on the number of individuals of each species showed that the fish community structures were not distinctively different between the habitats. Results of this study suggest that heavily exploited mangrove area can be rehabilitated through reforestation and can serve as fish habitat comparable to a natural mangrove.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2005
Keywords: Mangrove fisheries -- Philippines -- Cogtong Bay; Mangrove forests -- Philippines -- Cogtong Bay; Fishes -- Habitat -- Philippines -- Cogtong Bay